Detection of Crimean-Congo Haemorrhagic Fever virus antibodies in cattle in Kenedougou and Mouhoun provinces in Burkina Faso - Laibane Dieudonne Dahourou; Madi Savadogo; Mikhailou Kiswend-sida Dera; Lamoussa Roland Abga; Bruno Lalidia Ouoba; Rayangnewênde Stephane Arnaud Tapsoba; Bernadette Yougbare; Salimata Akio; Lamouni Habibata Zerbo; Amadou Traore; Rianatou Bada Alambedji (Open Veterinary Journal)
Background: Crimean-Congo haemorrhagic Fever (CCHF) is a zoonotic disease caused by an Orthonairovirus of the Nairoviridae family transmitted by tick bites and also contact with infected blood, tissues or body fluids. Until now, fewer studies have been conducted in animals in Burkina Faso. Aim: This study was conducted to investigate the seroprevalence and risk factors of CCHF in two provinces of Burkina Faso. Methods: Serum samples were collected from 371 bovine animals. In addition, questionnaire surveys were performed with cattle breeders. The double-antigen sandwich ELISA test was used to determine the presence of antibodies against the CCHF virus in serum samples. Results: The results showed an overall prevalence of 72.2% (95% CI: 67.6% - 76.7%). Within the 74 herds included in the study a herd prevalence of 96% (95% CI: 91.4% - 100%) was obtained. The prevalence was significantly higher in Mouhoun province (80%, 95% CI: 74% - 86%) compared to Kenedougou province (65.6%, 95% CI: 59.1% -72.2%). Multivariable regression analysis showed that females were more likely to be infected (OR=1.99, 95% CI: 1.1-3.6, p=0.023) than males. In addition, cross-breed animals (OR= 6.42, 95% CI: 1.71-24.14, p=0.006) were more likely to be infected compared to local-bred animals. This study revealed the presence of antibodies of CCHF virus in cattle in the study area, indicating the need of implementing control measures in veterinary sector. Conclusion: Despite the importance of CCHF in public health, no study has been implemented regarding this condition in animal in Burkina Faso. This study described evidence of cattle exposure to the virus in Burkina Faso. [Open Vet J 2024; 14(8.000): 1912-1920]